Retention of Nitrate-N in Mineral Soil Organic Matter in Different Forest Age Classes - Fuss, Colin B.; Lovett, Gary M.; Goodale, Christine L.; Ollinger, Scott V.; Lang, Ashley K.; Ouimette, Andrew P. (Ecosystems (New York), 2019)
Conceptual models of nutrient retention in ecosystems suggest that mature forests receiving chronically elevated atmospheric nitrogen (N) deposition should experience increased nitrate (NO₃⁻) losses to streams. However, at the Hubbard Brook Experimental Forest (New Hampshire, USA), recent stream NO₃⁻ concentrations have been unexpectedly low in mature watersheds. Poorly understood retention of NO₃⁻-N in soil organic matter (SOM) may explain this discrepancy. The relative availability of C and N in SOM influences NO₃⁻-N retention and may vary during succession due to processes of N mining and reaccumulation. To evaluate the strength of the SOM sink for NO₃⁻-N, we applied a 15 NO₃⁻ tracer to the mineral soil in eight stands spanning a forest chronosequence from about 20 years to old growth (≫ 200 years). We tracked ¹⁵N recovery in SOM 3 tracer to the mineral soil in eight stands spanning a forest chronosequence from about 20 years to old growth (200 years). We tracked 15 N recovery in SOM fractions in the upper 10 cm of B horizon over 5 weeks. Overall, forest age did not directly control the 5-week recovery of ¹⁵N, but it had an indirect effect via its influence on SOM properties such as C/N. Old-growth forest soils had the lowest C/N, implying closer proximity to effective N saturation. Across sites, both the particulate-and mineral-associated SOM fractions rapidly incorporated ¹⁵N, but recovery in each fraction generally declined with time, reflecting the dynamic nature of SOM. These results indicate that mineral horizons can provide an important N sink through the short term in forests of all ages, but that SOM-N remains subject to active cycling and potential loss from the soil pool over the longer term.